The Limits of Mind and “The Bignetti Model” - Bignetti, Enrico (New Horizons in Education and Social Studies Vol. 9, 2021)
Mind is so far limited that cannot give us an objective picture of the reality. Even, the sophisticated instruments invented by it, can give only a subjective perspective of the reality. An example is given by exploring “Neural Correlates to Consciousness” (NCC); by these means, we can highlight the plain route from brain to mind by exploring only the physiological, functional aspects of Consciousness, while the objective, scientific definition of it remains a groundless hope for an unsurmountable conflict of interest. This unresolved conflict mainly gives rise to three false dualisms in mind that emerge one from the other, like in a Matrioska. In each individual, the illusion of the existence of a Free-Will-possessing Self is the main outcome of this dualistic perspective of his mind. Yet, how comes that cognitive processes are so efficacious in daily life? “The Bignetti Model” is a cognitive model that explains how cognition can occur, in five compulsory steps, just on the base of these mental illusions.